Oxygen Sensing in Health and Disease - Prabhakar, Nanduri R.; Kumar, Ganesh K. (Current Respiratory Medicine Reviews, 2006)
Carotid bodies are the sensory organs for detecting systemic hypoxia and the ensuing reflexes prevent the development of tissue/cellular hypoxia. Reflexes arising from carotid body play important roles in pathophysiology involving chronic hypoxia. The purpose of this article is to: a) present a brief overview of the current concepts of O2 sensing by the carotid body, and b) how chronic intermittent hypoxia (CIH) such as that seen in recurrent apneas affects the carotid body function and its consequences on physiological systems. Hypoxic sensing in the carotid body requires an initial transduction step involving O2 sensor(s) and transmitter(s) for subsequent activation of the afferent nerve ending. The proposed O2 sensors in the carotidbody include heme containing enzymes and O2 sensitive K+ channels. It has been proposed that transduction process involves interactions between heme-containing proteins and O2-sensitive K+ channel proteins functioning as a “chemosome”. Hypoxia releases both excitatory and inhibitory transmitters from the carotid body. Excitatory transmitters contribute to afferent nerve activation by hypoxia, whereas inhibitory transmitters prevent over excitation. Thus, excitatory and inhibitory transmitters act in concert like a “push-pull” mechanism. CIH augments the hypoxic sensory response of the carotid body and induces a novel form of plasticity manifested as sensory long-term facilitation. Available evidence indicates that increased generation of reactive oxygen species (ROS) mediate CIH-induced functional form alteration in the carotid body. It has been proposed that CIH-induced functional alterations in the carotid body contribute to cardio-respiratory morbidities associated with CIH caused by recurrent apneas.
Keywords: push-pull mechanisms